Association of VARS2‐SFTA2 polymorphisms with the risk of chronic hepatitis B in a Korean population. (10th January 2015) - Cheong, Hyun Sub; Lee, Jeong‐Hoon; Yu, Su Jong; Yoon, Jung‐Hwan; Lee, Hyo‐Suk; Cheong, Jae Youn; Cho, Sung Won; Park, Neung Hwa; Park, Byung Lae; Namgoong, Suhg; Kim, Lyoung Hyo; Shin, Hyoung Doo; et al.
Abstract Background & Aims Hepatitis B virus (HBV) infection is the most serious risk factor for chronic hepatitis B (CHB), cirrhosis, and hepatocellular carcinoma. Recently, several genome‐wide association studies (GWASs) identified important variants associated with the risk of CHB in Asian populations. Specifically, our previous GWAS identified the VARS2‐SFTA2 gene region as one of the genetic risk loci for CHB. Methods To further characterize this association and to isolate possible causal variants within it, we performed an additional association study by genotyping more SNPs in the vicinity of the VARS2 and SFTA2 genes. In all, 14 SNPs of VARS2‐SFTA2 were analysed among a total of 3902 subjects (1046 cases and 2856 controls). Results Logistic regression analysis revealed that six SNPs, including the previously reported rs2532932, were significantly associated with the risk of CHB (P = 1.7 × 10−10~0.002). Further linkage disequilibrium and conditional analysis identified two variants (rs9394021 and rs2517459) as new markers of genetic risk factors for CHB rather than the reported SNP from our previous study (rs2532932). To evaluate the cumulative risk for CHB based on all known genetic factors, genetic risk score (GRS) were calculated. As anticipated, the distribution of the number of risk alleles in cases vs. controls clearly differed according to the GRS. Similarly, the odds ratios (ORs) were increased (OR = 0.32–3.97). Conclusion Our findings show that common variants in the VARS2‐SFTA2 gene region are significantly associated with CHB in a Korean population, which may be useful in further understanding genetic susceptibility to CHB.